Rural Literacies: Toward Social Cartography - Michael Corbett; Kim Donehower (Journal of Research in Rural Education, 2017)
In this article we analyze the emergence of the fi eld of rural literacies. We attempt to map this fi eld in a way that illustrates the foundational ideas of literacy and rurality as relational concepts, which are devoid of meaning as what we call "singularities." Our insistence on the importance of context and place reveals multiple rural literacies instantiated in a diverse range of studies that have emerged from foundational texts in the fi eld. In an eff ort to apply a spatial lens to rural literacies scholarship, we problematize authoritative decontextualized conceptions of both literacy and rurality. In doing so, we seek to place rurality on the map as an educationally and culturally signifi cant category in the analysis of literacy and education.